Economics: An Emerging Small World? - Sanjeev Goyal; Marco van der Leij; Jose Luis Moraga (Tinbergen Institute, 2004)
This paper examines the small world hypothesis. The first part of the paper presents empirical evidence on the evolution of a particular world: the world of journal publishing economists during the period 1970-2000. We find that in the 1970's the world of economics was a collection of islands. Two decades later, in the 1990's the world of economics was much more integrated, with the largest island covering close to half of the population. At the same time, the distance between individuals on the largest island had fallen significantly. Thus we believe that economics is an emerging small world.An exploration of the micro aspects of the network yields three findings: one, the average number of co-authors is very small but increasing; two, the distribution of co-authors is very unequal; and three, there exist a number of `stars', individuals who have a large number of co-authors. Thus the economics world is a set of inter-connected stars.We take the view that individuals decide on whether to work alone or with others; this means that individual incentives should help us understand why the economics world has the structure it does. The second part of the paper develops a simple theoretical model of co-authorship. The main finding of the model is that in the presence of productivity differentials and a shortage of high productivity individuals, inter-connected stars will arise naturally in equilibrium.
Keywords: A14; D20; J41; L22; O30; 330; small world; economics research; networks; coauthorship; hierarchy; Wirtschaftswissenschaft; Bibliometrie; Netzwerk; Welt